Ration Balancing: A Practical Strategy for Reducing Enteric Methane Emission and Carbon Footprint of Milk in India: A Review - Sherasia, Pankaj L.; Garg, Manget Ram (Indian Journal of Animal Nutrition, 2018)
Enteric methane is the largest contributor to the total greenhouse gas emissions from agricultural sector. It is closely related to the feed regime and the productivity of dairy animals. Life cycle assessment study indicated that the extensive dairy production system with low milk yields has higher carbon footprint of milk than more intensive system with higher milk yields. In this paper, various methane mitigation strategies have been discussed under Indian feeding and management conditions. These strategies are mainly focused onfeeding, breeding and rumen manipulation which can be broadly grouped into those that increase animal productivity and those that directly modify rumen fermentation so that less methane is produced in total. However, most of these strategies are not practically and commercially applicable for reducing methane emissions in large ruminants under field conditions owing to their various limitations. Further, many of these strategies require years of research before practical application and commercially viable products or technologies are available. For India, enteric methane mitigation strategy should be cost-effective and address socio-economic issues. Ration balancing helps in improving productivity and reducing enteric methane emissions in cows and buffaloes at farmers’ doorstep. A life cycle assessment study of milk production in India indicated that a significant reduction in carbon footprint of milk has been observed after feeding a balanced ration. Thus, improving animal productivity through ration balancing with available feed resources could be amost practical strategy for reducing enteric methane emissions and carbon footprint of milk production in India.